ECONOMIC OPPORTUNITIES FOR SANTRI COOPERATIVES THROUGH THE PONDOK PESANTREN LAW AL-MAWARDI PEGANTENAN PASANGGAR - Badrut Tamam; M. Munir (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
This research examines the economic opportunities and challenges of student cooperatives at Al-Mawardi Islamic Boarding School (Pondok Pesantren) from the perspective of internal institutional regulations. Student cooperatives are economic institutions that play a strategic role in supporting students' economic independence and providing practical learning about Islamic economic systems. This study employs a descriptive qualitative method with a case study approach, analyzing cooperative operations based on the internal laws and regulations of Al-Mawardi Islamic Boarding School. Data were collected through in-depth interviews, observations, and documentation studies of institutional regulations and cooperative reports. The findings reveal that student cooperatives have significant opportunities in developing the boarding school's economy through enhanced Islamic financial literacy, economic empowerment of students, and development of business networks based on Islamic values. However, several major challenges exist, including limited business capital, fluctuating member participation due to the boarding school education system, complexity of regulations that must align with sharia principles, and limited managerial competencies among cooperative administrators. This research recommends strengthening institutional capacity, enhancing synergy with boarding school stakeholders, and developing business models adaptive to the dynamics of boarding school life.